Lauraceae from the restingas of the state of Rio de Janeiro, Brazil. - Kropf, Marcela Stuker (2016)
This study presents the taxonomic study of the Lauraceae species in the restingas of Rio de Janeiro State. Our work provides an identification key, description, data on phenology, geographic distribution, commentary and illustrations. Twenty-five species subcategorized in nine genera were recognized: Aiouea Aubl., Aniba Aubl., Cassytha L., Endlicheria Nees, LicariaAubl., Nectandra Rol. ex Rottb., Ocotea Aubl., Persea Mill. and RhodostemonodaphneRohwer ex Kubitzki. The number of species was high with ten new occurrences, showingthat Lauraceae is among the top 20 most important Families for the restinga. Ocotea, thegenus of highest specific richness, is among the twelve most important genera in the restingasof the state of Rio de Janeiro.